Inaugural pink October mammogram screening campaign in hospital UiTM (HUiTM) Puncak Alam - Arbian, Nurzatul Azmira; Ab Mumin, Nazimah; Ramli Hamid, Marlina Tanty (Faculty of Medicine, 2021)
October is the month of breast cancer awareness and is popularly symbolized with the pink breast cancer awareness ribbon. This month is intended to empower women to step up their efforts in the prevention and early detection of breast cancer, primarily through regular mammograms and at the same time to support and celebrate breast cancer survivors. Statistics from Malaysian National Cancer Registry showed that breast cancer is the most common cancer and accounts for 34.1% of all cancers amongst females in Malaysia. Screening mammography examination is recommended for early detection of breast cancer in women over 40. Unfortunately, the number of women undergoing screening mammograms in Malaysia is still low compared to developed countries like the United States. According to the National Health and Morbidity Survey in 2019, three in four women in Malaysia aged 40 and above never had a mammogram.